The location of descending fibres to sympathetic preganglionic vasomotor and sudomotor neurons in man. - Nathan, P W (1987)
Evidence is given of the location in the spinal cord of man of the central sympathetic fibres supplying vasomotor and sudomotor neurons of the body caudal to the head and neck. The evidence is based on anterolateral cordotomies. The fibres lie within the medial part of the equatorial plane, extending from the base of the posterior horn and the lateral horn across the medial half of the white matter. The evidence from a previous paper together with that of the present paper is that the pathway maintains this position throughout the spinal cord as far as the L2 segment. The sympathomotor fibres caudal to the head and neck are supplied from both sides of the cord: sympathetic activity is not removed, although it may be slightly diminished, by a hemisection of the cord. The evidence suggests that sympathetic fibres for vasomotor control leave the cord cranial to the Th 7 segment. The knowledge of the location of the pathways is of value to neurosurgeons so that they may be avoided in the operation of anterolateral cordotomy.